Early Childbirth and Under-Five Malnutrition in Bangladesh - Onagoruwa, Adenike; Wodon, Quentin (World Bank, Washington, DC, 2017)
In Bangladesh, more than three in ten children under the age of five are stunted; but for children born of mothers younger than 18, the risk of stunting is higher. controlling for socio-economic and other characteristics, being born of a mother younger than 18 increases the likelihood of stunting for children under-five by five percentage points in the baseline model, as compared to otherwise similar children born of older mothers.